Electrical transport properties of (Pr1-xLax)0.7Sr0.3MnO3 (0 ≤ x ≤ 0.3) polycrystalline ceramics prepared by sol-gel process for potential room temperature bolometer use. Issue 4 (March 2020) - Pu, Xingrui; Li, Hongjiang; Dong, Gang; Chu, Kaili; Zhang, Shuai; Liu, Yang; Yu, Xiaohan; Liu, Xiang
Abstract: High density (Pr1- x La x )0.7 Sr0.3 MnO3 (PLSMO, x  = 0, 0.10, 0.20, 0.25, and 0.30) polycrystalline ceramics were fabricated by the sol-gel method followed by sintering at 1723 K for 12 h. The doping effects of lanthanum on structural, surface morphology and electrical transport properties of obtained ceramics were systematically investigated. X-ray diffraction patterns (XRD) confirmed that all samples crystallized in typical single orthorhombic perovskite phase with Pnma space group. Field emission scanning electron microscopy (FESEM) showed slight increase in grain size, and energy dispersive spectroscopy (EDS) mapping displayed uniformly distributed elements on the sample surface. Resistivity dependence of temperature ( R - T ) curves of PLSMO specimens were investigated by standard four-probe method, and results indicated decline in resistivity with the increase in La content. In addition, as the lanthanum doped content increased, the metal-insulator transition temperature ( T p ) improved significantly. The average ionic radius increased as Pr 3+ ions were replaced by La 3+ ions with larger ion radius, which further affected the Mn–O band angle and Mn–O band length. These changes enhanced the double-exchange interaction, increasing T p value. The temperature coefficient of resistance ( TCR ) curves revealed that peak TCR temperature improved with La content rose. The peak TCR temperature of PLSMO at molar ratio x  = 0.25 was significantly increased from 258.47 K to 299.37 K (room temperature 300 K) and value reached 5.03% K − 1 . Obviously, obtaining relatively high room temperature TCR value in Pr system materials was interesting as this was not observed previously. In sum, the proposed (Pr0.75 La0.25 )0.7 Sr0.3 MnO3 ceramics look potential candidates for use in advanced room temperature uncooled infrared bolometers.